2019
DOI: 10.1097/ta.0000000000002304
|View full text |Cite
|
Sign up to set email alerts
|

Echo is a good, not perfect, measure of cardiac output in critically ill surgical patients

Abstract: BACKGROUND Compared with a pulmonary artery catheter (PAC), transthoracic echocardiography (TTE) has been shown to have good agreement in cardiac output (CO) measurement in nonsurgical populations. Our hypothesis is that the feasibility and accuracy of CO measured by TTE (CO-TTE), relative to CO measured by PAC thermodilution (CO-PAC), is different in surgical intensive care unit patients (SP) and nonsurgical patients (NSP). METHODS Surgical patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…While SV cm is superior to BSA based methods it still has a PE of 33%, which is higher than the recommend threshold of 30%. Also, the root mean square error is +/− 13, which could be important in assessing metrics like stroke volume variation, but this is in line with the error reported in multiple studies comparing TTE to PAC in measurement of CO which range from 23 to 40% [7]. This study is describing one step in automating SV assessment with echo, further work is needed evaluate and improve the technique.…”
Section: Discussion/conclusionsupporting
confidence: 72%
See 3 more Smart Citations
“…While SV cm is superior to BSA based methods it still has a PE of 33%, which is higher than the recommend threshold of 30%. Also, the root mean square error is +/− 13, which could be important in assessing metrics like stroke volume variation, but this is in line with the error reported in multiple studies comparing TTE to PAC in measurement of CO which range from 23 to 40% [7]. This study is describing one step in automating SV assessment with echo, further work is needed evaluate and improve the technique.…”
Section: Discussion/conclusionsupporting
confidence: 72%
“…There are several reasons automating LVOTD in the measurement of SV could improve POC-TTE. It would increase the yield of the metric, especially in difficult to image surgical patients [7]. It could also prove to make SV assessment more accurate because LVOTD measurement is difficult, prone to error, and the value is squared (SV = π (LVOT D/2) 2 x LV VTI).…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Olivieri et al demonstrated good correlation and agreement among cardiac output measurements in both medical and surgical patients through the use of PACs and point-of-care TTE. 9 No monitoring device will innately improve patient outcomes, unless used by a clinician able to synthesize the clinical information and coupled with the appropriate treatment. Zarragoikoetxea et al echo this nicely in demonstrating that TTE can aid both in the diagnosis of LCOS and to further assess the response to intervention.…”
mentioning
confidence: 99%